(untitled) (Revista Venezolana de Salud Pública, 2018)
In order to determine the prevalence of Burnout Syndrome, occupational risk to develop it in the health personnel and the user’s opinion about on medical attention, a descriptive cross-sectional study was carried out in San Francisco’s Type I Ambulatory. The sample consisted of 17 workers and 120 users. Two instruments were used to collect data addressed to health personnel: ISTAS questionnaire (CoPsoQ) 2000 short version and Maslach Burnout Inventory and a third questionnaire to users that measured opinion about medical care. For Psychosocial Risk in the staff, a favorable level was found in the categories active work and self-development possibilities with 88.2% as well as a social support and quality of leadership of 64.7%; the unfavorable level was presented in the categories insecurity 58.8%, double presence 47% and estimated 47%. Likewise, it was highlighted that no worker presented Burnout syndrome since the dimensions of personalization and depersonalization with 88.2% were located at a low level. In turn, 90.9% of the users felt totally satisfied with the medical care, deducting that the factors that contributed to feelings of exhaustion or stress did not influence the quality of care provided in the premises. This served to project new studies and make new references regarding the Burnout syndrome and its scope, giving the pertinent recommendations, both to the community and to the ambulatory staff to reduce the risks of developing the disease.